“No Damn Black Gown Sons of Bitches among Them”: Rough Music and the Counter-Pastoral in the Eighteenth-Century Carolina Backcountry - Allan KULIKOFF (E-REA)
“Rough music,” according to English historian E. P. Thompson, included “raucous, ear-shattering noise, unpitying laughter, and the mimicking of obscenities.” These were sounds that the ruling class of the Carolina backcountry heard when confronted by their inferiors. This article examines the 18th century diary of a genteel Englishman, Charles Woodmason. At first a planter and merchant, he received Anglican ordination in the 1760s, and, as an itinerant minister, he traveled throughout the region. He heard vile sounds which he interpreted as rough music, often aimed at him. Just as the 18th century English pastoral reflected class antagonisms—the conflicts between landed gentry and rural capitalists—Woodmason’s Carolina counter-pastoral reflected cultural conflicts between backcountry Presbyterian and Baptist farmers and rich lowcountry Anglican gentlemen. Though he borrowed the yen for improvement common in England and tropes of class privilege from English pastorals, he wrote about neither deserted villages nor nostalgic yearning for a lost world of swains and husbandmen. The silence and seeming absence of slaves, along with the savagery of poorer whites, points to Woodmason’s southern identity.